The ECB's New Multi-Country Model for the euro area: NMCM - with boundedly rational learning expectations - Alistair Dieppe; Alberto González Pandiella; Stephen Hall; Alpo Willman (European Central Bank (ECB), 2011)
Rational expectations has been the dominant way to model expectations, but the literature has quickly moved to a more realistic assumption of boundedly rational learning where agents are assumed to use only a limited set of information to form their expectations. A standard assumption is that agents form expectations by using the correctly specified reduced form model of the economy, the minimal state variable solution (MSV), but they do not know the parameters. However, with medium-sized and large models the closed-form MSV solutions are difficult to attain given the large number of variables that could be included. Therefore, agents base expectations on a misspecified MSV solution. In contrast, we assume agents know the deep parameters of their own optimising frameworks. However, they are not assumed to know the structure nor the parameterisation of the rest of the economy, nor do they know the stochastic processes generating shocks hitting the economy. In addition, agents are assumed to know that the changes (or the growth rates) of fundament variables can be modelled as stationary ARMA (p,q) processes, the exact form of which is not, however, known by agents. This approach avoids the complexities of dealing with a potential vast multitude of alternative mis-specified MSVs. Using a new Multi-country Euro area Model with Boundedly Estimated Rationality we show this approach is compatible with the same limited information assumption that was used in deriving and estimating the behavioral equations of different optimizing agents. We find that there are strong differences in the adjustment path to the shocks to the economy when agent form expectations using our learning approach compared to expectations formed under the assumption of strong rationality. Furthermore, we find that some variation in expansionary fiscal policy in periods of downturns compared to boom periods.
Keywords: C51; D83; D84; E17; E32; 330; bounded rationality; Expectation; heterogeneity; imperfect information; Learning; macro modelling; open-economy macroeconomics